ANALISIS BUDAYA MUTU UNIVERSITAS SURABAYA DALAM RANGKA PENGUKURAN EFEKTIVITAS PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2008 - Naya Adi Swaputri; Muhammad Rosiawan; M. Arbi Hadiyat (Perpustakaan Universitas Surabaya, 2014)
University of Surabaya is a college that implement ISO 9001. However, the application of ISO 9001 will be successful if supported by organizational culture change in a positive direction. Total Quality Management or the development of quality culture requires line managers to change the style, way of working and even behavior as far as possible in order to get out of traditional organizational structures. It is necessary for testing to determine the extent of the influence of ISO 9001 at the University of Surabaya against existing quality culture in the organization by the method of Structural Equation Modeling (SEM). The purpose of this study was to measure the quality culture, knowing the relationship of cultural change with the implementation of ISO 9001 quality, and provide suggestions for improvement in organizational performance UBAYA thus be effectively and efficiently and to create a cultural change that brings quality UBAYA towards positive direction. Results obtained from this research is the application of ISO 9001:2008 proven direct impact positively on the quality of cultural change in UBAYA of 50.04 % . The results of the questionnaire and the great close relationship models that will be used as a reference in determining the repair using the method of Quality Function Deployment . Variable ISO 9001 that must be fixed first is the management system approach with a weight of 0.341 , the second is the process approach with a weight of 0,332 and the latter is employee engagement with a weight of 0.326 . From the results obtained Quality Function Deployment major repairs done by looking at the importance of how the value of more than 636.19875 . The improvement of priority is establishing quality objectives in accordance with the vision and mission UBAYA , distribute tasks employees are multitasking in a single unit of work , and make the effectiveness of the program with clear criteria and involving all employees.